Keynesian and neoclassical closures in an agent-based context - Bill Gibson (University of Massachusetts, Department of Economics, 2008)
Since the closure debate of the 1980s it is well known that comparative static derivatives in analytical macro models are highly sensitive to the closure rule selected. This led Keynesians to conclude that Keynesian closures were superior to those favored by the orthodoxy and vice-versa. It is argued that with the advent of agent-based or multi-agent systems, the closure debate is superseded. While elements of both Keynesian and neoclassical models survive the transition to the more synthetic environment, an agent-based approach eliminates the need for drastic simplification that was at the root of the debate from the beginning.
Keywords: 330